2004
DOI: 10.1097/00001786-200407000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment of Nurses in the Workplace

Abstract: Nurses who are sexually harassed at work face frustration and emotional and economic consequences. Historically before the 1970s, nurses had little legal recourse and tolerated sexual harassment as a necessary "evil" associated with working. The Civil Rights Act of 1964 created the option for legal remedies for sexual harassment/discrimination cases. Successful court cases established the legal criteria for sexual harassment. This article discusses the history, definition, high profile cases, research, consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
37
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 14 publications
10
37
0
1
Order By: Relevance
“…These findings are in agreement with previous research that indicated a higher prevalence of symptoms of depression amongst faculty members 3,4,6,12) . Research that relates experiences of abuse and harassment to depression and other mental health effects, though available, is limited.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are in agreement with previous research that indicated a higher prevalence of symptoms of depression amongst faculty members 3,4,6,12) . Research that relates experiences of abuse and harassment to depression and other mental health effects, though available, is limited.…”
Section: Discussionsupporting
confidence: 93%
“…In order to combat these pervasive problems, a comprehensive and multi-sectorial approach that combines institutional justice initiatives, reformed health policies and preventative educational programs are needed 26) . Furthermore, developing written guidelines, policies, and education programs designed to set standards for acceptable behaviors in educational settings have proven to be effective in changing norms 12) . It is important to note that changing the attitudes and norms that are entrenched in a society require sustained commitment and effort from all sectors 12,26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These values were lower than most reports in previous international studies, whereas the previous studies investigated the annual or lifetime prevalence. For the studies focused on nurses, some of them reported that physicians or other coworkers were identified as the primary perpetrators of SH 7,18,29) . Other literature demonstrated that the most common perpetrators in all types of SH were patients, followed by doctors or other staff 12,25) .…”
Section: Discussionmentioning
confidence: 99%